A (Blurry) Vision of the Future: How Leader Rhetoric about Ultimate Goals Influences Performance - Carton, Andrew M.; Murphy, Chad; Clark, Jonathan R. (Academy of Management Journal, 2014)
One key responsibility of leaders involves crafting and communicating two types of messages—visions and values—that help followers understand the ultimate purpose of their work. Although scholars have long considered how leaders communicate visions and values to establish a sense of purpose, they have overlooked how these messages can be used to establish a shared sense of purpose, which is achieved when multiple employees possess the same understanding of the purpose of work. In this research, we move beyond the traditional focus on leader rhetoric and individual cognition to examine leader rhetoric and shared cognition. We suggest that a specific combination of messages—a large amount of vision imagery combined with a small number of values—will boost performance more than other combinations because it triggers a shared sense of the organization's ultimate goal, and, in turn, enhances coordination. We found support for our predictions in an archival study of 151 hospitals and an experiment with 62 groups of full-time employees. In light of these findings, we conducted exploratory analyses and discovered two dysfunctional practices: leaders tend to (1) communicate visions without imagery and (2) over-utilize value-laden rhetoric.